REACCION TUBERCULINICA EN NIÑOS DE UNO A CUATRO AÑOS DE EDAD VACUNADOS CON BCG. LAMBAYEQUE-PERU - Soto Cáceres, Víctor (2024)
Considering the discrepancies about the quality ofBCG vaccine applied in our environment and the utility of PPD as a diagnostic method for the tuberculosis infection. We realized the present investigation to determine the tuberculine reactivity prevalence in children between 1 to 4 years old vaccinated with BCG and evaluate indirectly the PPD utility. In the city of Lambayeque we evaluated a total of 569 children between 1 to 4 years old vaccinated with BCG. They received PPD 2 UT in accordance with standarised rules of the OMS/OPS. The results show a high prevalence of negative response to PPD in 90 % of the total of children. We do not found significative difference between age groups, heaping up or nutrition degree for the tubercullne response. With this results, lt Is neccesary the reevaluatlon of the oficial international criteria about the use of PPD as a diagnostic method of natural tuberculosis lnfection beca use the vacclne do not produce distortions in our environmenL